Corporate Board Diversity and Sustainability Reporting: A Study of Selected Listed Manufacturing Firms in Nigeria - Helen Obiageli Anazonwu; Francis Chinedu Egbunike; Ardi Gunardi (Indonesian Journal of Sustainability Accounting and Management, 2018)
The objective of the study is to ascertain the influence of corporate board diversity on sustainability reporting on a sample of quoted manufacturing firms in Nigeria. The study adopts a panel research design. The population of the study comprised quoted manufacturing companies on the Nigerian Stock Exchange. This was restricted to companies classified under conglomerates, consumer goods, and, industrial goods sector. The study used secondary data, extracted from the annual reports of the studied manufacturing companies. Fixed effects panel regression analysis was used to test the hypotheses. The dependent variable sustainability reporting was measured using an Economic, Social, and Governance (ESG) index, the independent variables were board member nationality, proportion of women directors, proportion of non-executive directors, and multiple directorships. The results show no significant positive influence of board member nationality, while proportion of women directors, proportion of non-executive directors, and multiple directorships were significant. The study recommends among others, the adoption of NSE Sustainability Disclosure Guidelines for a unified integrated reporting framework for Nigerian firms, secondly, a heterogeneous board composition, which can leverage on the diverse set of skills of board members.